Changes of Crocin and Other Crocetin Glycosides in Saffron Through Cooking Models, and Discovery of Rare Crocetin Glycosides in the Yellow Flowers of Freesia Hybrida - Shindo, Kazutoshi; Sakemi, Yuka; Shimode, Saki; Takagi, Chiharu; Uwagaki, Yohei; Hattan, Jun-ichiro; Akao, Miu; Usui, Shiori; Kiyokawa, Ayako; Komaki, Masako; Murahama, Minoru; Takemura, Miho; et al. (Frontiers in Nutrition, 2022)
Crocetin glycosides such as crocin are noted as functional food materials, since the preventive effects of crocin have been reported against chronic disease and cancer. However, it is unclear how these apocarotenoids are structurally changed through cooking for our intake. We examined such changes of crocetin glycosides (crocin, tricrocin, and crocin-3) contained in saffron (stigmas of Crocus sativus) through cooking models. These glycosides were almost kept stable in boiling for 20 min (a boiled cooking model), while hydrolysis of the ester linkage between glucose and the crocetin aglycone occurred in a grilled cooking model (180°C, 5 min), along with a 13-cis isomerization reaction in a part of crocetin subsequently generated. We further here revealed that the yellow petals of freesia (Freesia x hybrida) with yellow flowers accumulate two unique crocetin glycosides, which were identified to be crocetin (mono)neapolitanosyl ester and crocetin dineapolitanosyl ester. A similar result as above was obtained on their changes through the cooking models. Utility applications of the freesia flowers as an edible flower are also suggested in this study. Additionally, we evaluated singlet oxygen (1O2)-quenching activities of the crocetin glycosides contained in saffron and freesia, and crocetin and 13-cis crocetin contained in the grilled saffron, indicating that they possessed moderate 1O2-quenching activities (IC50 24 – 64 microM).